Valorization of food innovations with territorial identity. - Cendón, Maria Laura (2023)
The implementation of food valorization tools with territorial identity, such as protected designations of origin, has had multiple territorial effects, highlighting territorial governance processes, quality improvements, as well as technological, organizational and environmental care innovations. The aim of this article is to identify and value the innovation processes that are generated from the implementation of a Protected Designation of Origin (PDO) of olive oil in Andalusia, Spain. A synthetic indicator of innovation and environmental practices was constructed, based on information collected via surveys carried out in mills and interviews to key actors. The results showed differences between the mills that have PDO and those that do not have the seal. The DOP mills reached higher average values in the indicators of innovation and greater homogeneity, mainly in the oil production process. The values were lower in aspects related to organizational-commercial innovations and product differentiation. However, in terms of environmental practices, mills with PDO have not registered statistically significant differences with respect to mills that do not have the sign of quality.